2022
DOI: 10.2147/copd.s367701
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Recent Exacerbation History on the Efficacy of Once-Daily Single-Inhaler Fluticasone Furoate/Umeclidinium/Vilanterol Triple Therapy in Patients with Chronic Obstructive Pulmonary Disease in the FULFIL Trial

Abstract: Background In the FULFIL trial, once-daily single-inhaler triple therapy with fluticasone furoate/umeclidinium/vilanterol (FF/UMEC/VI) resulted in reduced moderate/severe exacerbation rates and conferred significant improvements in lung function and health status in patients with chronic obstructive pulmonary disease (COPD) versus twice-daily budesonide/formoterol (BUD/FOR) dual therapy. Methods FULFIL was a Phase III, randomized, double-blind, double-dummy, parallel-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In our observational study, we also observed a reduction in the annualized rate of any (moderate/severe) exacerbation following the initiation of FF/UMEC/VI in the BUD/FORM subgroup; a high proportion of patients had experienced ≥ 1 exacerbation in the prior year and these patients experienced a reduction in any exacerbation as well. In FULFIL, a reduction in the annualized rate of severe exacerbations was observed at 24 weeks in patients treated with FF/UMEC/VI versus BUD/FORM with an exacerbation in the year prior to study entry [ 14 ]. In our study, we also observed a significant reduction in severe exacerbations in patients with ≥ 1 exacerbation during baseline following the initiation of FF/UMEC/VI in the BUD/FORM subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…In our observational study, we also observed a reduction in the annualized rate of any (moderate/severe) exacerbation following the initiation of FF/UMEC/VI in the BUD/FORM subgroup; a high proportion of patients had experienced ≥ 1 exacerbation in the prior year and these patients experienced a reduction in any exacerbation as well. In FULFIL, a reduction in the annualized rate of severe exacerbations was observed at 24 weeks in patients treated with FF/UMEC/VI versus BUD/FORM with an exacerbation in the year prior to study entry [ 14 ]. In our study, we also observed a significant reduction in severe exacerbations in patients with ≥ 1 exacerbation during baseline following the initiation of FF/UMEC/VI in the BUD/FORM subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, prior exacerbations are well-recognized as a strong predictor of future exacerbation risk [ 18 ]. KRONOS did not require patients to have an exacerbation in the previous year (74% of patients did not) [ 14 ]; FULFIL required patients to have ≥ 2 moderate exacerbations or ≥ 1 severe exacerbation in the previous year if their FEV 1 was ≥ 50–< 80%, but did not require exacerbations in the previous year if their FEV 1 was < 50% (35% of patients did not) [ 15 , 19 ]. Considering these studies are supposedly similar in other key aspects according to Ismaila et al, it is surprising and contrary to accepted scientific knowledge on the impact of prior exacerbations that the annual moderate/severe exacerbation rate was > 50% higher for BUD/FOR in KRONOS versus FULFIL (0.55 vs. 0.34), when 74% of KRONOS patients had no exacerbations in the previous year [ 14 , 15 ].…”
Section: Key Summary Pointsmentioning
confidence: 99%
“…One difference was that IMPACT only included patients with recent exacerbations, and the annual moderate/severe exacerbation rate with FF/UMEC/VI was 0.91 [ 20 ]. However, in a post hoc analysis of FULFIL, the annual moderate/severe exacerbation rate in patients with recent exacerbations before study entry (aligned with IMPACT) was 0.19 with FF/UMEC/VI [ 19 ], approximately 80% lower than in IMPACT. This again highlights that FULFIL is somewhat of an outlier, with fundamental differences to its connected studies; this questions how these studies could be considered similar and why heterogeneity was not further explored.…”
Section: Key Summary Pointsmentioning
confidence: 99%